Analisis Sistem Informasi Akuntansi Arus Kas Pada Badan Amil Zakat Nasional (Baznas) Kota Gorontalo - Sudirman, Sudirman (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This study aims to analyze the Cash Flow Accounting Information System in the National Zakat Agency (Baznas) of Gorontalo City in terms of PSAK 109 of 2009 and ED PSAK 02 revised in 2009. In this study a descriptive analysis of the data obtained. In this study it was found that the cash flow information system in the Gorontalo City National Amil Zakat Agency was in accordance with PSAK 109 in 2008. However, the cash outflow report must refer to the revised PSAK 02 in 2009. However, the recording of cash outflow has not been made yet. As appropriate, because the accounting system for cash outflows must refer to the revised 2009 ED PSAK 02, which is the cash outflow activity is divided into 3 namely operational activities, investment activities and financing activities. While the Gorontalo City Baznas only reports 2 activities, namely operational and investment activities. As for funding activities he reported. In addition, in the process of distributing and reporting financial data such as changes in non-legal funds, reports of changes in assets under management are not presented even though these transactions often occur.